An examination of the auditing law proposal, suggesting a review instead of an audit for micro companies in Finland - Haapamäki, Elina (Palgrave Macmillan, 2025)
This study uses qualitative methods to analyze stakeholder comment letters concerning a Finnish legislative proposal to replace mandatory audits with less stringent review engagements for micro companies. The study explores lobbying incentives and public interest discourse surrounding this regulatory change, which aimed to reduce administrative burdens for small businesses. Findings reveal overwhelming opposition to the reform, primarily due to concerns that it would decrease financial reporting quality, cause confusion, and potentially facilitate the gray economy. Stakeholders largely preferred retaining traditional financial statement audits or moderately increasing audit exemption thresholds rather than adopting the proposed review mechanism. This paper contributes to auditing literature by examining how policymakers addressed the tension between reducing regulatory burdens on small businesses and maintaining the quality of financial reporting.
Keywords: Review assurance; Harmonization; Regulation; fi=Laskentatoimi|en=Accounting|